Metode Dongeng dengan Boneka Tangan untuk meningkatkan Keterampilan Menyimak Siswa Sekolah Dasar - Suwardi, Suwardi; Puspita Sari, Wahyu (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
Listening is a language skill that plays an important role in human life and student learning success. This research aims to test the effect of the storytelling method with hand puppets on the listening skills of elementary school students. This type of research uses true experimental. Research procedures include problem identification, implementation of treatment, data analysis, and ending with drawing conclusions. Samples were taken by purposive sampling. The test questions as the main instrument have been declared valid and reliable. Data analysis used the Shapiro Wilk statistical formula, F test, t-test, and regression test. This research concludes that the storytelling method with hand puppets has a positive influence on listening skills in grade Istudents of SDN in Juwana District, Pati Regency, Central Java. Theoretically, the results of this research strengthen the view of behavioristic learning theory and found 10 steps of learning activities in the fairy tale method with hand puppets which include; 1) preliminary activities; 2) pre-test; 3) the teacher explains the elements in the fairy tale; 4) the teacher tells a story according to the reading text; 5) students practice working on questions; 6) the teacher asks about the elements of the fairy tale contained in the story; 7) students read the text according to the theme of the fairy tale; 8) students identify the attitudes of the characters contained in the reading text; 9) post-test; and 10) closing activities